The impact of bone channel entrance selection within the footprint region of the femoral anterior cruciate ligament on the achievement of near isometric ACL reconstruction in rabbits - Zhang, Jiating; Xu, Chengfeng; Wang, Jiangtao; Zhang, Jia; Zhao, Gang; Liu, Liu; Li, Chunbao; Liu, Yujie (Frontiers in Surgery, 2025)
IntroductionConstruction of an animal model of rabbit anterior cruciate ligament (ACL) near isometric reconstruction is a basic condition to study the patterns of graft stress and tendon to bone healing. The impact of alterations in the bone tunnel entrance within the femoral footprint region on graft tension remains uncertain. The objective of this study was to determine the femoral tunnel entrance that provides the closest approximation to near-isometric reconstruction within the femoral ACL footprint.Materials and methodsEighteen Cadaveric rabbit knees were used in this experiment. The semitendinosus autografts were employed for ACL reconstruction. Six knees were reconstructed using the middle position of the femoral footprint area as the entrance (Mi-tunnel), six knees used a position 2 mm anterior to the middle (An-tunnel), and six knees used a position 2 mm posterior to the middle (Po-tunnel). All grafts were pretensioned with 10 N at 150° and 90° flexion and firmly fixed at the tibial end. The change in graft strain was measured under maximum flexion and extension in the rabbit knee joints.ResultsUnder a maximum flexion of 150° and 10 N pretension, the graft strain decreased significantly during knee extension in the An-tunnel and Mi-tunnel groups and there was no significant decrease in the Po-tunnel group. There were significant differences in graft strain between the Po-tunnel and An-tunnel during knee extension at 135°–35° (P < 0.05). Under 90° flexion and 10 N pretension, the Po-tunnel group showed a minimal change in graft strain compared to the An-tunnel and Mi-tunnel groups with knee extension and flexion (135°–35°) except at the initial pretension Angle. There was a statistically significant difference in graft tension when the Po-tunnel compared to the An-tunnel (P < 0.05).ConclusionsThe Po-tunnel within the femoral footprint region may be the best choice for ACL near isometric reconstruction in rabbits.